A multiple criteria evaluation system for bankruptcy prediction of small and medium-sized enterprises - Oliveira, M. D N. T. (2018)
The global financial crisis has shown the ability to predict bankruptcy to be a vital management skill, and that the methodologies used for that purpose should be as close to reality as possible. This study aims to develop a multiple criteria system to predict bankruptcy in small and medium-sized enterprises (SMEs). It combines cognitive mapping with the measuring attractiveness by a categorical based evaluation technique (MACBETH), resulting in a more complete and transparent process for evaluating SMEs (and their risk of bankruptcy). What differentiates this framework from previous ones is the fact that it is based on information obtained directly from managers and bank analysts who deal with this type of adversity on a daily basis. The results highlight the importance of financial and strategic aspects, among others; and demonstrate how cognitive mapping can improve the understanding of the decision situation at hand, while MACBETH facilitates the calculation of trade-offs among evaluation criteria.